Import competition and industry location in a small-country model of productivity growth - Colin R. Davis; Ken-ichi Hashimoto (Osaka University, Institute of Social and Economic Research (ISER), 2019)
We study the effects of import competition on industry locations patterns in a small open economy with two regions. Domestic productivity growth converges to the international rate through firm-level investment in process innovation. With firms locating production and innovation in their lowest cost locations, the concentration of industry in the larger region is linked with firm-level innovation through an import competition effect that is increasing in the market share of imported goods and the productivity differential of domestic firms with the rest of the world. We show that increased import competition, through either a larger number of imported goods or a faster international rate of productivity growth, leads to greater industry concentration by reducing domestic market entry and decreasing the relative productivity of domestic firms. We also consider the implications of improved regional and international economic integration.
Keywords: F12; F43; O40; R12; 330; Import competition; Industry concentration; Endogenous productivity growth